Integration of melanopsin signals into visual pathways - Barrionuevo, Pablo Alejandro (2019)
Anatomical studies showed that melanopsin-containing ipRGCs project to the LGN, however, how melanopsin photopigment activation integrates into the Magnocellular (MC), Parvocellular (PC) and Koniocellular (KC) pathways is not understood. To study this, we have implemented three approaches, including natural image statistics analysis, pupillary recordings, and psychophysical testing. Principal component analysis of nine hyperspectral images revealed that optimal combinations of photoreceptors involved intrusion of melanopsin signals in the three postreceptoral pathways. Flickering pupillary recordings (1Hz) showed melanopsin activation combines linearly in the MC and KC pathways but nonlinearly in the PC pathway. Psychophysical testing showed melanopsin modulations of sinusoidal temporal contrast sensitivity, especially of the MC pathway at 3Hz for 2000 td. Our results demonstrated that all three visual pathways are affected by melanopsin activation but in different fashion and extent.